Neurotoxicity of high-dose methotrexate in the treatment of non-Hodgkin’s lymphomas in children: clinical and genetic aspects - Z. K. Simavonyan; T. T. Valiev; A. L. Kashanina; V. V. Semenova; A. R. Zheleznyak; L. Serdan Ramos; A. Yu. Ikonnikova; T. V. Nasedkina (Онкогематология)
Backround. Treatment protocols for non-Hodgkin’s lymphomas in pediatric patients include a combination of cytotoxic drugs, with methotrexate (MTX) playing a central role, often administered in high doses (1000–5000 mg/m2). MTX is associated with a wide range of side effects, manifesting as organ toxicity (hemato-, hepato-, neuro-, nephrotoxicity, mucositis, infectious complications). Neurotoxicity poses a significant challenge in real clinical practice. The pathogenesis of neurological complications is not fully understood, making investigations into potential predictive factors for neurotoxicity development, as well as methods for its prevention and treatment, highly relevant.Aim. To analyze clinical, laboratory and instrumental data in the development of MTX-induced neurotoxicity and to identify potential predictive factors.Materials and methods. This study presents an analysis of literature data on MTX neurotoxicity and our own clinical cases of non-Hodgkin’s lymphomas patients who developed severe neurological complications following MTX- containing treatment regimens. Non-Hodgkin’s lymphoma diagnosis was verified according to the clinical guidelines of the Ministry of Health of the Russian Federation. Antitumor treatment and supportive care were administered according to B-NHL-BFM 95 or ACCL NII DOG-2003 protocols. The severity of toxicities was assessed using the National Cancer Institute (USA) Common Terminology Criteria for Adverse Events. All patients underwent genetic testing by allelespecific hybridization on a biological microarray. The study material was DNA extracted from peripheral blood lymphocytes. The timing of blood samples collection was not standardized.Results. Neurological complications associated with high-dose MTX therapy can manifest as seizures, stroke-like symptoms, aphasia, and other neurological deficits. T2-weighted and FLAIR magnetic resonance imaging sequences reveal hyperintense signals in the white and gray matter of the brain. In the four presented clinical cases, neurological complications included Wernicke’s encephalopathy and encephalitis. Genetic testing in 3 patients revealed the heterozygous A allele of MTHFR rs1801133. In addition, one patient was found to have the heterozygous G allele of MTHFR rs1801131. All patients had the heterozygous G/A genotype in the SLC19A1 rs2838958 gene, and three patients had the heterozygous C/T genotype of SLC19A1 rs1051266. Heterozygous T/C genotype and homozygous C/C genotype were also identified for SLCO1B1 rs4149056.Conclusion. The risk of neurotoxicity is determined by the pharmacological characteristics of MTX and, possibly, genetic factors. This study demonstrates that neurological complications during MTX-containing therapy are heterogeneous, often life-threatening, and require a multidisciplinary approach. The obtained data on genetic polymorphisms may become an effective tool in predicting the development of neurotoxicity.